2014
DOI: 10.1177/1362168814541737
|View full text |Cite
|
Sign up to set email alerts
|

A teacher’s first language use in form-focused episodes in Spanish as a foreign language classroom

Abstract: This study investigates a teacher’s L1 use during focus-on-form episodes (FFEs). FFEs assist L2 learning by bringing learners’ attention to language. We studied the language used in FFEs in a Spanish as a foreign language (SFL) classroom to better understand the pedagogical purposes of L1 use in the classroom. We video-recorded 12 hours of an intermediate-high SFL classroom with an L1 English teacher at a US university. The audio data was segmented into FFEs and then coded (English L1, Spanish L2, mix) to refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 34 publications
0
23
0
1
Order By: Relevance
“…The literature on the L1 use in the L2 classroom has targeted various L2s (e.g., Spanish by Nakatsukasa & Loewen (2015); French by Hennebry, Rogers, Macaro, & Murphy (2013); German by Kaushik, 2013) and different directions, such as grammar instruction (e.g., Ghaiyoomian & Zarei, 2015;Aslikhosh, 2014;Damra & Al Qudah, 2012), writing instruction (e.g., Berming, 2016;Kim and Yoon 2014), students' perceptions (e.g., Debreli & Oyman, 2016;Al Sharaeai, 2012;Nazary, 2008) and teachers' perceptions (e.g., Karimian & Mohammadi (2015); Ahmed (2015); Mohebbi & Alavi, 2014). The present literature review focuses on studies on EFL vocabulary instruction for relevance with the current study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature on the L1 use in the L2 classroom has targeted various L2s (e.g., Spanish by Nakatsukasa & Loewen (2015); French by Hennebry, Rogers, Macaro, & Murphy (2013); German by Kaushik, 2013) and different directions, such as grammar instruction (e.g., Ghaiyoomian & Zarei, 2015;Aslikhosh, 2014;Damra & Al Qudah, 2012), writing instruction (e.g., Berming, 2016;Kim and Yoon 2014), students' perceptions (e.g., Debreli & Oyman, 2016;Al Sharaeai, 2012;Nazary, 2008) and teachers' perceptions (e.g., Karimian & Mohammadi (2015); Ahmed (2015); Mohebbi & Alavi, 2014). The present literature review focuses on studies on EFL vocabulary instruction for relevance with the current study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding the context of this study, the utilisation of the L1 in the English classroom is also inevitable. This is because the use of L1 is common when teachers share similar L1 with the students, (Nakatsukasa & Loewen 2014). English teachers in Malaysia may have the tendency to use BM for specific functions (micro-functions) since majority of them speak BM.…”
Section: Micro-functions Of L1 In the L2 Classroommentioning
confidence: 99%
“…Some descriptive studies have shown that in a spoken foreign language classroom, the instructor often incorporates learners’ L1 when describing vocabulary items (e.g. Nakatsukasa & Loewen, 2015; Polio & Duff, 1994; Tang, 2002). For example, Nakatsukasa and Loewen (2015) examined teachers’ use of learners’ L1 in focus-on-form episodes (FFEs) in a Spanish as a foreign language classroom.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Nakatsukasa & Loewen, 2015; Polio & Duff, 1994; Tang, 2002). For example, Nakatsukasa and Loewen (2015) examined teachers’ use of learners’ L1 in focus-on-form episodes (FFEs) in a Spanish as a foreign language classroom. In their 12-hour-long class recording, they found a significant relationship between the teacher’s language choice and the FFE’s linguistic areas.…”
Section: Review Of Literaturementioning
confidence: 99%